2017
DOI: 10.1016/j.canep.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in the AGRICAN cohort study (2005–2011)

Abstract: We found a decreased incidence for tobacco-related cancers and an increased incidence of prostate cancers, skin melanoma and multiple myeloma. Specific subgroups had a higher cancer incidence related to occupational status and pesticide use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 40 publications
1
39
0
5
Order By: Relevance
“…Data from the Norwegian population indicated a significantly decreased standardised incidence ratio of 0.42 3. Two large agricultural cohorts confirmed these findings: the Agricultural Health Study (AHS) among pesticide applicators4 and the AGRIculture and CANcer (AGRICAN) cohort among French farmers 5. Two explanations were given for these results: (1) a lower prevalence of smoking in farmers compared with the general population, especially among farm owners6 and (2) exposure to livestock, which could be a protective factor,7–10 possibly in relation with endotoxins 11…”
Section: Introductionmentioning
confidence: 82%
“…Data from the Norwegian population indicated a significantly decreased standardised incidence ratio of 0.42 3. Two large agricultural cohorts confirmed these findings: the Agricultural Health Study (AHS) among pesticide applicators4 and the AGRIculture and CANcer (AGRICAN) cohort among French farmers 5. Two explanations were given for these results: (1) a lower prevalence of smoking in farmers compared with the general population, especially among farm owners6 and (2) exposure to livestock, which could be a protective factor,7–10 possibly in relation with endotoxins 11…”
Section: Introductionmentioning
confidence: 82%
“…Among studied pesticides, atrazine, imazethapyr, metolachlor, mancozeb, lindane, Agent Orange, MCPA, dinoseb, 2,4‐D, 2,4,5‐T, ioxynil, dichlorprop, DDT, fenitrothion, maneb, triadimefon, alachlor, pentachlorophenol, organochlorine insecticides, and organophosphate insecticides (malathion, diazinon, chlorpyrifos, and terbufos) were cited. Besides that, 6 studies verified phenoxy herbicides exposure and 11 studies did not define a specific type of pesticide . In addition, heterogeneity was present when the association between pesticide exposure and HNC was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 32 selected studies, 50% were conducted in European countries, 47% in North America, 9% in Oceania, and 6% in Asia . No studies were found in Latin America and Africa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations